Common sense model of self-regulation for understanding adherence and quality of life in type 2 diabetes with structural equation modeling. Issue 1 (January 2021) - Fall, Estelle; Chakroun-Baggioni, Nadia; Böhme, Philip; Maqdasy, Salwan; Izaute, Marie; Tauveron, Igor
Highlights: Illness perceptions are linked to adherence via treatment necessity-concerns. Perceived threat is linked to avoidant coping, and negative health outcomes. Perceived control is liked to vigilant coping, and positive health outcomes. Control and threat perceptions are potential levers for action (self-care; adherence). Acceptance influences diabetes management and should be addressed by interventions. Abstract: Objectives: The objective of the present study was to test the Common Sense Model of self-regulation (CSM) for its relevance for improving adherence and quality of life in type 2 diabetes. Methods: A sample of 253 patients with type 2 diabetes was recruited. They completed questionnaires about their perceptions regarding diabetes, coping strategies, therapeutic adherence and quality of life. Their HbA1c levels were also collected. Structural equation modeling (SEM) was used to check the adequacy of our theoretical model (CSM) with the patient data. Results: The final model indicated that perceptions were directly and indirectly related to health outcomes through coping strategies and adequately matched the data (χ 2 / df = 561/ 220 = 2.55; RMSEA = 0.08; PCFI = 0.66; PGFI = 0.70). Moreover, the model appeared to be identical for both types of treatment (oral and injectable). Conclusions: Illness perceptions and coping strategies, or, more specifically, how patients accept disease and think they are able to manage it, significantly affect therapeutic adherence and quality of life in type 2 diabetes. Practice implications: These results pave the way for developing psychological treatments aimed at improving patient acceptance and internal resources (e.g. use of autobiographical memory, Acceptance and Commitment Therapy).